INFUSION OF NERVE GROWTH FACTOR (NGF) INTO KITTEN VISUAL CORTEX INCREASES IMMUNOREACTIVITY FOR NGF, NGF RECEPTORS, AND CHOLINE ACETYLTRANSFERASE IN BASAL FOREBRAIN WITHOUT AFFECTING OCULAR DOMINANCE PLASTICITY OR COLUMN DEVELOPMENT - SILVER, M. A. (2001)
Intracerebroventricular or intracortical administration of nerve growth factor (NGF) has been shown to block or attenuate visual cortical plasticity in the rat. In cats and ferrets, the effects of exogenous NGF on development and plasticity of visual cortex have been reported to be small or nonexistent. To determine whether locally delivered NGF affects ocular dominance column formation or the plasticity produced by monocular deprivation in cats at the height of the critical period, we infused recombinant human NGF into the primary visual cortex of kittens using an implanted cannula minipump. NGF had no effect on the normal developmental segregation of geniculocortical afferents into ocular dominance columns as determined both physiologically and anatomically. The plasticity of binocular visual cortical responses induced by monocular deprivation was also normal in regions of immunohistochemically detectable NGF infusion, as measured using intrinsic signal optical imaging and single-unit electrophysiology. Immunohistochemical analysis of the basal forebrain regions of the same animals demonstrated that the NGF infused into cortex was biologically active, producing an increase in the number of NGF-, TrkA-, p75(NTR)-, and choline acetyltransferase-positive neurons in basal forebrain nuclei in the hemisphere ipsilateral to the NGF minipump compared to the contralateral basal forebrain neurons. We conclude that NGF delivered locally to axon terminals of cholinergic basal forebrain neurons resulted in increases in protein expression at the cell body through retrograde signaling.